2022
DOI: 10.3390/polym14153038
|View full text |Cite
|
Sign up to set email alerts
|

Role of Biomaterials Used for Periodontal Tissue Regeneration—A Concise Evidence-Based Review

Abstract: Periodontal infections are noncommunicable chronic inflammatory diseases of multifactorial origin that can induce destruction of both soft and hard tissues of the periodontium. The standard remedial modalities for periodontal regeneration include nonsurgical followed by surgical therapy with the adjunctive use of various biomaterials to achieve restoration of the lost tissues. Lately, there has been substantial development in the field of biomaterial, which includes the sole or combined use of osseous grafts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 129 publications
0
14
0
Order By: Relevance
“…Osteogenesis and vascularization have been used to regenerate the alveolar bone that supports the teeth [ 231 , 233 ]. In addition to bone regeneration, the wound-healing process is also applicable for regenerating the soft tissue that covers the periodontium [ 2 , 233 , 234 ].…”
Section: Biomedical Applications Of the Therapeutic Agent-loaded Fibr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Osteogenesis and vascularization have been used to regenerate the alveolar bone that supports the teeth [ 231 , 233 ]. In addition to bone regeneration, the wound-healing process is also applicable for regenerating the soft tissue that covers the periodontium [ 2 , 233 , 234 ].…”
Section: Biomedical Applications Of the Therapeutic Agent-loaded Fibr...mentioning
confidence: 99%
“…Fibrous scaffolds exhibit excellent characteristics, including adjustable biodegradability, appropriate mechanical properties, and high porosity, which make them promising materials for use in regenerative medicine [ 1 , 2 , 3 ]. In addition to providing a suitable environment for cell growth [ 4 ], these scaffolds offer flexibility for drug loading [ 5 ], enabling them to be used as implantable [ 6 ] and degradable drug carriers [ 7 ] for treating diseases and repairing tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The need for HA for bone grafts has significantly increased in response to the rise in occurrences of alveolar bone loss [18][19][20]. This problem necessitates creating and investigating substitute HA materials for bone graft raw materials made from natural materials.…”
Section: Introductionmentioning
confidence: 99%
“…The beta tricalcium promote the regeneration of the bone. It basically dematerlised the phosphate and calcium ions that ultimately [7][8] stimulate the formation of the new bone. It is observed that the regeneration of tissues in the periodontal area is not an easy task.…”
Section: Introductionmentioning
confidence: 99%